PENGELOLAAN KINERJA TENAGA PENDIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN - Tanjung, Wardah Kholilah; Julia, Ayu Putri; Nasution, Hafiz Yusuf; Batubara, Rahmad Riadi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
This article discusses managing the performance of teaching staff in an effort to improve the quality of education. Educators and educational staff have a strategic role in shaping national character and improving the quality of human resources in the era of globalization. Effective performance management includes coaching, development, promotion, transfer, compensation and assessment of teaching staff. This research uses a literature review method by collecting data from various related literature references. The results of the analysis show that good performance management can improve teachers' professional competence, which includes personality, professional, social and pedagogical aspects. Thus, optimal performance management contributes to improving the quality of learning and achieving national education goals.